Technology for diagnostic sonography : Study guide and laboratory exercises - e uthor; Wagner, Paul R. (St Louis Missouri: Elsevier, 2013)
Helps you gain a foundation for sonography practice. Corresponding to the chapters in Hedrick's "Technology for Diagnostic Sonography", this guide focuses on basic concepts to help you master sonography physics and instrumentation. It includes laboratory exercises designed to teach you how to operate a scanner.
Section I: Fundamental Concepts 1. Properties of Sound Waves 2. Interactions of Ultrasound with Tissue 3. Intensity 4. Single Element Transducers: Properties 5. Single Element Transducers: Transmission and Echo Reception 6. Static Imaging 7. Image Formation in Real-Time Ultrasound 8. Real-Time Ultrasound Transducers 9. Real-Time Ultrasound Instrumentation 10. Digital Signal and Image Processing 11. Image Quality in Real-Time Ultrasound 12. Real-Time Image Artifacts 13. Doppler Physics and Instrumentation 14. Pulsed-Wave Doppler Spectral Analysis 15. Doppler Imaging 16. M-Mode 17. Clinical Safety 18. Performance Testing Appendix A: Computer Appendix B: Hemodynamics Appendix C: Contrast Agents Section II: Laboratory Exercises Lab 1 Display Depth, Frame Rate, Freeze Frame, Cine Loop Lab 2 Overall Gain and Output Power Lab 3 Time Gain Compensation Lab 4 Frequency and Penetration Lab 5 Transmit Focus Lab 6 Magnification (Write Zoom) Lab 7 Dynamic Range Lab 8 Persistence Lab 9 Gray-Scale Mapping Lab 10 Distance and Area Measurements Lab 11 Doppler Controls I Lab 12 Doppler Controls II Lab 13 Doppler Angle to Flow Lab 14 Nyquist Limit and Aliasing Lab 15 Color Controls I Lab 16 Color Controls II Lab 17 Application Presets Lab 18 Tissue-Mimicking Pphantom Section III: Review Tests Review Questions Answers to Review Questions with Explanations Glossary of Key Terms
Keywords: Diagnostic ultra sonic imaging; Ultrasonics in medicine; Diagnostic utrasonic imaging instruments; Ultrasonography -- Methods ultrasonics